2019
DOI: 10.1016/j.desal.2019.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and simulation of the dual stage pressure retarded osmosis systems

Abstract: Utilization of renewable energy sources, as an approach to reduce greenhouse gas (GHG) emissions, have been globally popular in the last few decades. Among renewable energy sources, pressure retarded osmosis (PRO) has been scrutinized by scientists since the mid 70's. However, even today, the existing river-sea PRO systems can only marginally meet the generally approved criterion of 5 W/m 2 power density, a threshold for an economically feasible PRO system. As an approach to increase the performance of PRO sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 139 publications
(205 reference statements)
0
4
0
Order By: Relevance
“…Nevertheless, if the river water-seawater pairing is replaced with wastewater-desalination brine, a 2-fold increase in the extractable specific energy could be expected because of the much higher osmotic gradient between two solutions. In another module-scale analysis carried out by Soltani and Struchtrup [ 121 ], it was found that a dual-stage system showed improvement in comparison to a single-stage system in terms of specific energy generation.…”
Section: Existing Cfd Models and Their Challengesmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, if the river water-seawater pairing is replaced with wastewater-desalination brine, a 2-fold increase in the extractable specific energy could be expected because of the much higher osmotic gradient between two solutions. In another module-scale analysis carried out by Soltani and Struchtrup [ 121 ], it was found that a dual-stage system showed improvement in comparison to a single-stage system in terms of specific energy generation.…”
Section: Existing Cfd Models and Their Challengesmentioning
confidence: 99%
“…Table 3 summarises the literature on modelling studies for PRO systems. Although some module-scale analyses are available [ 120 , 121 ], detailed 3D CFD modelling for the PRO process has yet to be investigated. The insight of 3D modelling is important for scaling up the PRO processes; thus, further modelling work for PRO is recommended.…”
Section: Existing Cfd Models and Their Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…A lot of effort is being made in that direction: Wan et al developed membranes with one of the highest power densities [19], Nagy et al modelled fouling mechanisms and the effects on PRO [20], Long et al gave indications about energetically optimal operation strategies [21]. Control strategies have also been proposed [22], as well as different process configurations [23], even integration with other processes, such as desalination [9], [17]. Taking into account these achievements and the expected solution to the current challenges, PRO is deemed to be a viable option [14] to exploit SGE at the location presented in this research.…”
Section: Introductionmentioning
confidence: 99%